Tổng hợp, nghiên cứu cấu trúc và tính chất của một số N-aryliđen[6-(2-hetarylvinyl)-3-oxo-piriđazin-2-yl]axetohiđrazit - Sơn, Trần Quốc; Đạt, Nguyễn Đăng; Thắng, Đàm Xuân (Vietnam Journal of Chemistry, 2014)
Twenty two N-arylidenehydrazides of [6-(2-hetarylvinyl)-3-oxopyridazine-2-yl] acetic acid have been synthesized starting from levulinic acid. Their structures have been confirmed by UV, IR, NMR and mass spectra. The spectral properties and the biological activity were investigated. Some of the tested compounds exhibit fungicidal and bactericidal activity at 25 µg/ml.